(untitled)
The process of economic development-in the sense of a sustained increase in per capita income-is typically associated with dramatic changes in some key economic variables relating to the sectoral composition of production, trade, and factor-use. And this seems to suggest that it is essentially a "disorderly" affair. Some of these changes have been observed regularly enough to qualify as the stylised facts, or the "regularities", of economic development. These general observations about the real world seem to support a spate of "disorderly" hypotheses about the nature of economic development. The critical minimum-effort hypothesis, the poles-of-development conjecture, the unbalanced-growth strategy of development, the propositions advocating a big-push, the great spurt, or the process of cumulative causation, all suggest that the development process may have been disequilibrating in the "structural sense" . Yet another dimension of such "disorderly" hypotheses is the pioneer’s vision of the effects of growth on income distribution. Thus Lewis’s "capital fundamentalism" envisages a particularly "bloody" scenario: capital accumulation proceeds relentlessly in his dual-economy model, where profits rise while real wages remain constant because the supply of labour-the Marxian "reserve army"-is (definitionally) elastic. In Lewis’s model, if not in the real world, the story of (capitalist) growth comes to an end once the real wage starts to rise; this must happen because, again by definition, the wage-earners consume all that they earl